2015
DOI: 10.1002/ejic.201403224
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Base‐Free Michael Addition at Room Temperature with Nickel‐Based Bifunctional Amido‐Functionalized N‐Heterocyclic Carbene Catalysts

Abstract: A series of nickel‐based chiral bifunctional catalysts (1d–3d) with N‐heterocyclic carbene (NHC) ligands derived from (1R)‐(–)‐menthol, (1S)‐(–)pinene, and (1R)‐(+)‐camphor have been successfully designed for asymmetric Michael addition reactions under base‐free conditions. The NHC complexes, namely, [1‐R‐3‐{N‐(phenylacetamido)}imidazol‐2‐ylidene]2Ni [R = (1S)‐menthyl (1d), (1S)‐pinane (2d), and (1R)‐isobornyl (3d)], bearing chiral ancillaries on the amido‐functionalized side arms of the NHC ligands, performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The mixture was stirred at 60 °C for 20 h. Ethanol was evaporated and the precipitated oxime filtrated under reduce pressure. The product was used without further purification [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was stirred at 60 °C for 20 h. Ethanol was evaporated and the precipitated oxime filtrated under reduce pressure. The product was used without further purification [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite their promise, the multistep sequences required for the synthesis of these fused bicyclic oxazolidine N‐heterocyclic carbene ligands has somewhat restricted the larger applicability of these ligands, and this has attracted our attention. Specifically, owing to our interest in the exploration of the catalytic utility N‐heterocyclic carbene ligands with different ring types, spanning from the ubiquitous five‐membered cyclic imidazole‐ and triazole‐based ones to less common varieties such as acyclic six‐membered N‐heterocyclic carbenes, bicyclic imidazo[1,2‐ a ]pyridines,, and tricyclic triazolooxazine‐derived ones, we became interested in exploring the catalytic exploits of one such less frequently encountered type, that is, chiral bicyclic oxazolidine‐fused N‐heterocyclic carbene ligands. Furthermore, as much of the catalytic studies reported for these bicyclic oxazolidine‐fused N‐heterocyclic‐carbene‐based systems were performed under in situ LAC conditions and there are no known examples of well‐defined transition‐metal complexes, we decided to employ structurally characterized molecular complexes for our study in asymmetric catalysis to obtain a better insight into the mode of action of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this purpose, a series of bis‐chelating amido‐functionalized N‐heterocyclic carbene complexes of nickel of the type (NHC) 2 Ni ( 1 – 3 ,23 4 – 8 ,24 11 – 12 25 and 13 –1 5 26) were synthesized, and in the process of which two rare examples of the terminal‐[Ni–OH] complexes 9 and 10 25 were structurally characterized (Figure 1). Significantly enough, all of these nickel complexes 1 – 15 of the amido‐functionalized NHC ligands carried out the bifunctional catalysis of the base‐free Michael addition reaction under ambient conditions at room temperature Scheme (A–C).…”
Section: 3 Base‐free Michael Addition Reactionmentioning
confidence: 99%
“…The asymmetric version of the base‐free Michael addition was also tried with the following chiral bifunctional Ni–NHC catalysts 13 – 15 26. Quite interestingly, of the three bifunctional catalysts derived from the (1 R )‐(–)‐menthol ( 13 ), (1 S )‐(–)pinene ( 14 ) and (1 R )‐(+)‐camphor ( 15 ) scaffolds, only the menthyl derivative 13 exhibited asymmetric induction exhibiting enantionselectivity of up to 75 % ( ee ) even though all of the three catalysts carried out the base‐free Michael addition in an efficient fashion.…”
Section: 3 Base‐free Michael Addition Reactionmentioning
confidence: 99%